2017
DOI: 10.15804/tner.2017.49.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solving Skills, Metacognitive Awareness, and Mathematics Achievement: A Mediation Model

Abstract: This study was aimed to identify the relationship between problem solving skills, metacognitive awareness, and mathematics achievement as well as to identify the role of metacognitive awareness as a mediator. This study involved a total of 333 Form Four students from ten secondary schools in Malaysia. Data were collected using questionnaires, while information about mathematics achievement was provided by the school management. Data were analyzed using the Structural Equation Modeling (SEM) technique. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Metacognitive skills and students' motivation are positively correlated to problem-solving abilities in chemical balance (Muna et al, 2017). Metacognitive awareness through problem-solving skills tend to affect mathematical achievements (Rahman & Hassan, 2017).…”
Section: Simultaneous Relationship Between Predictor Variables and Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Metacognitive skills and students' motivation are positively correlated to problem-solving abilities in chemical balance (Muna et al, 2017). Metacognitive awareness through problem-solving skills tend to affect mathematical achievements (Rahman & Hassan, 2017).…”
Section: Simultaneous Relationship Between Predictor Variables and Prmentioning
confidence: 99%
“…Yıldırım and Nur Ersozlu, (2013) reported that metacognitive awareness has a significant relationship with the level of mathematical ability. Its development aids students in solving mathematical problems (Rahman & Hassan, 2017). According to the results from studies conducted by Bars and Oral (2017), it was reported that the perceptions of any prospective teacher concerning metacognitive awareness are used to predict the level of problem-solving abilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, this also requires students' awareness of thinking to control and regulate their thinking processes. Problem-solving is a complex process that involves metacognition (Hassan & Rahman, 2017). Besides, practical problem solving can be obtained by providing opportunities for students to apply their metacognitive strategies when solving problems (Hassan & Rahman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving is a complex process that involves metacognition (Hassan & Rahman, 2017). Besides, practical problem solving can be obtained by providing opportunities for students to apply their metacognitive strategies when solving problems (Hassan & Rahman, 2017). Therefore, the process of metacognition is needed by students in solving math problems to increase their problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%
“…The problems of integration of Mathematics in teaching activity are the topic of the research by the scientists from different countries. Developing a model for integrated teaching of Mathematics and environmental education was covered in Cotič et al (2015), the relationship between problem solving skills, metacognitive awareness and Mathematics achievement was defined, and the role of metacognitive awareness as a mediator in Nurulhuda was clarified in Hassan & Rahman (2017), the concept of interdisciplinary integration in Sicherl Kafol (2007) was defined, the integrated integrated teaching of Mathematics in elementary school in Skupnjak (2009) was analyzed, the relationships between numerical content and algebraic thinking in Somasundram et al (2019) were investigated. They concluded that the implementation of an integrated approach to the use of computer technology in the formation of abilities to teach mathematics helps to increase the pedagogical competence of primary school teachers and knowledge of mathematical material.…”
Section: Introductionmentioning
confidence: 99%